ANALYSIS OF MATERIALS FOR RESTORATION OF BUILDINGS AND STRUCTURES ON THE RAILWAY TRANSPORT - Pshinko, O. M.; Krasniuk, O. V.; Palii, V. V. (Science and Transport Progress, 2007)
In the article is brought analysis of condition of buildings and erecting, which are used on the rail-freight traffic in theUkraine. Described main known dissolves, which are to be use for the transport building repair and buildings. Shown advantages of using as repair material polymer-cement and cement –polymer dissolves.